O júri simulado e o ensino de argumentação: suscitando o poder da fala - Ramalho , Joseane Batista de Azevedo (2023)
Undeniably, the school has the role of forming critical subjects and protagonists active in the social environment and who are involved in the resolution of collective demands and needs pertinent to public spaces, where students are inserted. With this, the student must be led to reflect, problematize and present his point of view in the face of the various social and communication situations, thus exercising the argumentation. In this scenario, the teaching of argumentation can contribute to form citizens aware of their social role and interact effectively in the most diverse situations of social use of the language. For this dissertation unveils its focus on argumentation under the linguistic bias, starting from the following problematic: How does the process of construction of the textual genre simulated jury occur, as an argumentative practice in the classroom? In view of this, this dissertation emphasizes the act of arguing through the didactic experience that the simulated jury genre in the oral modality provides. The objective of the research was to investigate the teaching-learning process of the textual genre simulated jury, mediated by didactic sequences and as an argumentative practice in the classroom. Thus, this dissertation presented an investigation on the teaching of oral production, with a theme related to violence against women (theme that was chosen by the students), using the procedure of the didactic sequence of Dolz et al. (2013c). The theoretical-methodological framework is based on the Theory of Linguistic Argumentation of Anscombre and Ducrot and collaborators (1987/1989), Perelman (1999); about discursive genres, Bakhtin (2000) and Marcuschi (2008); on the categories of orality is discussed from Marcuschi (2010) and Koch (2014), and on the textual genres and orality, from the perspective of Marcuschi (2008, 2010), in addition to the National Curricular Parameters (BRASIL, 1998) and the National Common Curricular Base (BRASIL, 2018). The research was of a qualitative and applied nature, from the perspective of action research. The investigation was developed in a state public school, in the city of João Pessoa, Paraíba, with students of the 9th grade of Elementary School Final Years, between the months of July and August 2022. As a result of this work, we had the elaboration of a didactic material aimed at the teacher, bringing the simulation of judgments, the approach with the oral argumentation and the proposal of intervention. The relevance of this research occurred with the discussion of the oral genre in the legal sphere, so that the students reached the linguistic-discursive competences, due to the intervention modules.